Effect of lower extremities position on volleyball attack take-off height - Martinez, A. C.; Marquez, Ni. A.; Hsieh, C. T. (ISBS Proceedings Archive (Michigan), 2021)
The purpose of this study was to investigate the influence of volleyball attack take-off technique on the centre of mass (CoM) take-off height. The kinematics of lower extremities at take-off was obtained via 3D motion analysis. Results showed that the group with greater normalised attack height (HA) had greater normalised CoM take-off height (p < 0.01) than the group with lower normalised attack height (LA). Additionally, the HA group had a greater inter-ankle distance at take-off (p < 0.05) than the LA group. There was no significant difference in CoM horizontal distance between the groups. The findings of this study indicate that the normalised CoM take-off height for a volleyball attack is neither influenced by the feet position at take-off nor by the horizontal CoM distance from take-off to ball impact.